Potassium methoxide/disilane-mediated formylation of aryl iodides with DMF at room temperature. Issue 24 (6th November 2020) - Wang, Haiyang; Tong, Xiaogang; Huo, Yanman; Tang, Jiaying; Xia, Chengfeng
Abstract : A formylation of aryl iodides at room temperature using a weaker base KOMe instead of BuLi was developed. Abstract : A formylation of aryl iodides at room temperature using a weaker base KOMe instead of BuLi was developed. The TMS-TMS disilane was discovered to play crucial roles in this formylation. It was found that the MeO − group of KOMe coordinated with two silyl groups of disilane to generate a hypercoordinate silane species. This hypercoordinate silane species reacted with aryl iodide to give an aryl carbanion, which underwent formylation with DMF to give an aryl aldehyde.